Facile synthesis and microstructure modulation of crystalline polymeric carbon nitride for highly boosted photocatalytic hydrogen evolution. Issue 14 (26th March 2020) - Wang, Wenbin; Shu, Zhu; Zhou, Jun; Meng, Dawei; Zhao, Zhengliang; Li, Tiantian
Abstract : Synchronous construction and microstructure-modulation of crystalline PCN were achieved via a facile vapor-deposition method. Abstract : Upgrading the melon-based bulk polymeric carbon nitride (PCN) into tri- s -triazine-based crystalline PCN has been proved effective and crucial to improve its intrinsic photocatalytic activity. Currently, facilitating the synthesis process of crystalline PCN and further optimizing its structure are challenging and have attracted increasing attentions. This work realized the facile one-step synthesis of K + -doped tri- s -triazine-based crystalline PCN with delicate box-shapes (KCCNB- x ), by heating melamine with KCl using a vapor-deposition approach. KCCNB-30 demonstrated greatly boosted visible-light photocatalytic H2 evolution (HER) activity which is 33 times that of BCN. This benefits mainly from the facilitated photo-exciton transfer in the tri- s -triazine-based crystalline framework as well as the further enhanced light absorption in the box shape of KCCNB-30. Additionally, the versatility of this strategy was proved via successfully synthesizing Na + -doped tri- s -triazine-based crystalline PCN with box-shapes.